SOLVENT EXTRACTION AND SEPARATION POSSIBILITIES OF Zr (IV) AND Fe (III)/Al (III) FROM HYDROCHLORIC ACID MEDIA WITH COMMERCIAL EXTRACTANTS - BHIKARI CHARAN BHATTA,; SUJATA MISHRA, (International Journal of Pharma and Bio Sciences, 2014)
The liquid-liquid extraction and separation of Zr(IV) and Fe(III) / Al(III) from hydrochloric acid solution (4M) using TOA( Tri-octyl amine), Cyanex 921(tri–n–octyl phospine oxide), Cyanex 923 (a mixture of four trialkyl phosphine oxides) and their binary mixture in kerosene was studied. The extraction of Zr(IV) increased with increase in concentration of Fe(III) or Al(III) in the aqueous phase in all the cases. The separation factors between zirconium (IV) and Fe(III) / Al(III) was maximum when binary mixture of 0.1M TOA and 0.01M Cyanex 923 was used as organic phase extractant. Stripping of Zr(IV) was quantitative using 0.2M HNO3 and 0.4M Na2CO3 when loaded organic phase contains Fe(III). Whereas 0.25M HNO3 and 0.55M Na2CO3 were found effective for stripping of Zr(IV) in the presence of Al(III).